The Integration of Digital Literacy into Indonesian Language Instruction to Enhance Students’ Academic Skills - Eli Eli; Ihwan Ridwan; Amaluddin Amaluddin; Andi Fadilah Humairah (Austronesian: Journal of Language Science & Literature, 2026)
Rapid advances in information technology require universities to transform their approaches to integrating digital skills into learning. This study aims to analyze the level of digital literacy among students in Indonesian language courses at Universitas Muhammadiyah Parepare (UMPAR) and to identify its contribution to academic performance. Unlike previous studies, which generally only mapped levels of digital literacy, this study offers a new contribution by empirically linking the three dimensions of digital literacy to patterns of their integration into teaching practices and their impact on academic achievement. The study employed a quantitative descriptive approach with 120 students in their third through fifth semesters as respondents. Data were collected through structured questionnaires, participatory observation, and documentation of learning activities, with variables covering the three dimensions of digital literacy: information access, content evaluation, and digital content production. The results indicate that UMPAR students possess good foundational skills in accessing digital information sources but still face significant challenges in evaluating and verifying the accuracy of content. Practices in producing digital academic content, such as writing online academic essays and creating multimedia presentations, are also not yet optimal. Correlation analysis revealed a significant positive relationship between digital literacy and academic ability (r = 0.54, p < 0.01), confirming that strengthening digital literacy contributes significantly to academic achievement. These findings underscore the need for more systematic learning strategies to develop all dimensions of digital literacy evenly, while also promoting the development of an Indonesian language curriculum that explicitly integrates digital literacy competencies as learning outcomes.